КОНЦЕПЦІЯ ПРОЕКТУВАННЯ ТЕАТРАЛЬНИХ ПЛАКАТІВ (Педагогіка вищої та середньої школи, 2007)
The method of the associative planning is expounded on the example of playbill fo r raising of tragedies V. Shakespeare.